Is It Time for a Multilateral Voluntary Carbon Offset Regulatory Agency? - , Enobong Udoh (Archives of Current Research International, 2017)
The aim of this paper is to identify the problem of dubious or fake Offset projects in the voluntary carbon market. Using primary data gotten from questionnaires sent out to 190 respondents in 2016, with the aid of descriptive analysis the results show overwhelmingly evidence that the issue of dubious Offsets is a real impediment to the deepening of the voluntary carbon market for which urgent action is needed. The paper recommends a multilateral type public regulator to sanitize the role of existing private regulators (auditors). This was supported by the views of the respondents, as it will strengthen the business motive – environmental sustainability model for a market approach towards reducing global Green House Gases emission levels.